Aktivnosti v naravi, dodana vrednost pri športni vzgoji na Fakulteti za strojništvo - Bratuž, Jože (Šport (Ljubljana), 2019)
Outdoor activities are a part of the Physical Education program at the Faculty of Mechanical Engineering for about 30 years. Physical education lecturers at the Faculty of Mechanical Engineering are successfully collaborating with teachers from other faculties of the University of Ljubljana in organizing outdoor activities. Every year we organize a five day alpine skiing course, one day skiing trips, hiking trips, sailing, camping and other activities. The participation of our students at these activities is very high. We consider, that the participation in outdoor activities has a positive effect on the personal development of our students.
Keywords: aktivnosti v naravi; Faculty of Mechanical Engeneering; Fakulteta za strojništvo; hiking; outdoor activities; physical education; pohodništvo; skiing; smučanje; sport; students; šport; športna vzgoja; študenti; University of Ljubljana; Univerza v Ljubljani